2018
DOI: 10.1016/j.isci.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Serine Phosphorylation by mTORC1 Promotes IRS-1 Degradation through SCFβ-TRCP E3 Ubiquitin Ligase

Abstract: SummaryThe insulin receptor substrate IRS-1 is a key substrate of insulin and insulin-like growth factor (IGF) receptor tyrosine kinases that mediates their metabolic and growth-promoting actions. Proteasomal degradation of IRS-1 is induced following activation of the downstream kinase mTOR complex 1 (mTORC1) to constitute a negative feedback loop. However, the underlying mechanism remains poorly understood. Here we report that Ser 422 of IRS-1 is phosphorylated by mTORC1 and required for IRS-1 degradation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 55 publications
2
59
1
1
Order By: Relevance
“…In recent years, it has also been suggested Handling Editor: E. Closs. that mTORc1 is able to phosphorylate upstream targets of the insulin signalling pathway in muscle, leading to inhibition of the pathway, and in turn impaired translocation of the GLUT4 glucose transporter to the plasma membrane (Yoneyama et al 2018). Thus, it has been proposed that a potential mechanism by which obesity-induced increases in blood BCAA concentrations could lead to the development of insulin resistance is through the chronic activation of mTORc1 suppressing insulin signalling in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has also been suggested Handling Editor: E. Closs. that mTORc1 is able to phosphorylate upstream targets of the insulin signalling pathway in muscle, leading to inhibition of the pathway, and in turn impaired translocation of the GLUT4 glucose transporter to the plasma membrane (Yoneyama et al 2018). Thus, it has been proposed that a potential mechanism by which obesity-induced increases in blood BCAA concentrations could lead to the development of insulin resistance is through the chronic activation of mTORc1 suppressing insulin signalling in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present the precise mechanism of IGF-I-induced IRS-1 protein degradation. The downstream kinase mTORC1 phosphorylates the serine residue of IRS-1 at amino acid 422; this phosphorylation recruits ubiquitin ligase, resulting in IRS-1 degradation (19). Given our data, we envisage a possible scenario: since the IRS-1 protein level is dynamically changed in response to IGF stimulation and varies in each cell, cells with higher IRS-1 levels are eliminated under physiological conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Because protein degradation of IRS-1 is induced by the activation of the downstream IGF signal kinase mTORC1 (16)(17)(18)(19), it is possible that the level of GFP-fused IRS-1 also degraded and the GFP signal diminished in response to IGF signal activation. To exclude this possibility, we generated stable cell lines expressing both mycIRS-1 and GFP independently (L6-mycIRS-1-GFP).…”
Section: Cells Overexpressing Irs-1 Were Selectively Excluded When Thmentioning
confidence: 99%
“…Insulin and insulin-like growth factors (IGFs), IGF-I and IGF-II, are mainly involved in muscle hypertrophy and play pivotal roles in growth, differentiation, survival, and various aspects of metabolism in a wide range of mammalian tissues [ 4 , 23 25 ]. Modulation of IGF-1 signaling is required for the downregulation of IRS-1 phosphorylation, and the P3K/AKT/mTOR signaling pathway activates IRS-1 degradation [ 33 ]. Activated AKT, in turn, phosphorylates and activates a second kinase, mTOR [ 4 , 16 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of IGF-1 signaling is required for the downregulation of IRS-1 phosphorylation, and the P3K/AKT/mTOR signaling pathway activates IRS-1 degradation [ 33 ]. Activated AKT, in turn, phosphorylates and activates a second kinase, mTOR [ 4 , 16 , 33 , 34 ]. In disagreement with previous reports [ 13 ], our data showed that ALA induced IRS-1 phosphorylation and subsequent stimulation of the PI3K/AKT pathway, resulting in activation of the p70S6 pathway in skeletal muscle of OLETF rats.…”
Section: Discussionmentioning
confidence: 99%